2008
DOI: 10.1124/mol.108.052019
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Breast Cancer Resistance Protein (BCRP)/Bcrp1 and Multidrug Resistance Protein 3 (MRP3)/Mrp3 Are Involved in the Pharmacokinetics of Resveratrol

Abstract: The phytoestrogen resveratrol has putative health-promoting effects and is present in several dietary constituents. Resveratrol is metabolized extensively in the gut epithelium, resulting in the formation of hydrophilic glucuronic acid and sulfate conjugates. These polar resveratrol conjugates need specific transporters to cross the cell membrane. We show here that vectorial transport of some of these metabolites is mediated by multidrug resistance protein 3 (MRP3, ABCC3) and/or breast cancer resistance protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 41 publications
9
105
0
Order By: Relevance
“…Transgenic mice deficient in BCRP exhibit greatly increased plasma bioavailability of resveratrol and its metabolites mediated by an enhanced absorption through gut epithelia [80]. Interestingly, not all of the ABC transporters efflux xenobiotics back into the gut lumen after oral consumption (see [6] for review and Fig.…”
Section: Polyphenols As Abc Transporter Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice deficient in BCRP exhibit greatly increased plasma bioavailability of resveratrol and its metabolites mediated by an enhanced absorption through gut epithelia [80]. Interestingly, not all of the ABC transporters efflux xenobiotics back into the gut lumen after oral consumption (see [6] for review and Fig.…”
Section: Polyphenols As Abc Transporter Substratesmentioning
confidence: 99%
“…For example, the MRP3 transporter pumps xenobiotics into the basolateral side (or blood side) of gut epithelia. Resveratrol is a substrate for this pump, and MRP3-deficient mice have been shown to have significantly decreased plasma levels of resveratrol and its metabolites following the oral consumption [80].…”
Section: Polyphenols As Abc Transporter Substratesmentioning
confidence: 99%
“…We have previously shown that lack of ABCG2 results in increased plasma levels of resveratrol and its metabolites in FVB/N mice (22). Hence, any antagonizing effects of this phytoestrogen on mammary tumor development should even be more pronounced in these ABCG2-deficient K14cre;Brca1 F/F ;p53 (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Residual intracellular resveratrol glucuronide is released through the serosa into the bloodstream by another multidrug resistanceassociated protein 3 (MRP3). MRP3 is an ABC-transporter that transports resveratrol and other polyphenolic compounds as well riboflavin and biotin into the bloodstream [31]. Once in the blood, resveratrol can be transported as the glucuronide bound to albumin [26,32].…”
Section: Bioavailability Of Resveratrolmentioning
confidence: 99%